The Continuations of Chrétien's Perceval content and construction, extension and ending - Tether, Leah ca. 20./21. Jh (Boydell & Brewer, 2012)
The notion of Continuation in medieval literature is a familiar one - but difficult to define precisely. Despite the existence of important texts which are commonly referred to as Continuations, such as Le Roman de la Rose, Le Chevalier de la Charrette and, of course, the Perceval Continuations, the mechanics and processes involved in actually producing a Continuation have found themselves indistinguishable from those associated with other forms of medieval réécriture. The Perceval Continuations (composed c.1200-1230) constitute a vast body of material which incorporates four separately authored Continuations, each of which seeks to further, in some way, the unfinished Perceval of Chrétien de Troyes - though they are not merely responses to his work. Chronologically, they were composed one after the other, and the next in line picks up where the previous one left off; they thus respond intertextually to each other as well as to Chrétien, and only one actually furnishes the story as a whole with an ending. Here, these fascinating texts are used as a lens for examining, defining and distinguishing the whole concept of a Continuation; the author also employs theories as to what constitutes an 'end' and what is 'unfinished', alongside scrutiny of other medieval 'ends' and Continuations. Dr Leah Tether is a Postdoctoral Research Fellow at the Cultures of the Digital Economy Institute, Anglia Ruskin University
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Chrétien / de Troyes / active 12th century / Criticism and interpretation; Chrétien -- de Troyes -- 1150-1190 -- Li contes del Graal; Arthurian romances / History and criticism; Literature, Medieval; Fortsetzung -- Literatur